PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada Mahasiswa Manajemen Bisnis Syariah Pengguna Smartphone Vivo Angkatan 2019 UIN Sjech M. Djamil Djambek Bukittinggi) - Miftia Holivina; Novera Martilova (CV. Adiba Aisha Amira, 2023)
This research is motivated by the emergence of various smartphone brands, therefore companies must be able to compete with other well-known products. This research was conducted to determine whether there is an effect of price and product quality on Vivo smartphone consumer satisfaction. This study aims to determine and analyze how much influence price has on customer satisfaction, how much influence product quality has on customer satisfaction, and how much influence price and product quality have on customer satisfaction. The type of research method used is the quantitative research method. With data collection techniques in the form of distributing questionnaires. The analysis technique used was instrument test, classical assumption test, multiple linear regression analysis and hypothesis testing. The research test was carried out using the SPSS 16 application which showed that first price had a significant effect on consumer satisfaction, which was indicated by a significantly smaller value than the alpha value (0.000 <0.05). So the first hypothesis is accepted. Second, product quality has no effect on consumer satisfaction, which is indicated by a significantly greater value than the alpha value (0.104 > 0.05). So the second hypothesis is rejected. In the results of the coefficient of determination (R2) a value of 0.737 is obtained, which means that the independent variables, namely price and product quality, have an effect on consumer purchase satisfaction of 73.7% while the remaining 26.3% are influenced by other variables not included in this study. This research is expected to help Vivo to pay attention to the price and quality of its products, and it is hoped that it can become a reference in the UIN SMDD Bukittinggi library.